Conceptualizing and Defining the Intention Construct for Future Physical Activity Research - Rhodes, R.; Rebar, Amanda (Lippincott Williams & Wilkins, 2017)
Â© 2017 Lippincott Williams & Wilkins. Intention has been an extremely important concept in physical activity theory and research but is complicated by a double-barreled definition of a decision to perform physical activity and the commitment to enact that decision. We put forth the hypothesis that these separate meanings have different measurement requirements, are situated in distinctly different intention-based models, and show discrete findings when explaining physical activity motives.